TOXICOHISTOPATHOLOGY IN FATAL WEEDICIDE POISONING A CASE SERIES (Journal of Forensic Medicine & Toxicology, 2025)
Paraquat is a herbicide widely utilized in agriculture. It poses significant public health challenges due to its high toxicity and associated mortality rate. Despite its classification as moderately hazardous by the WHO, its affordability and accessibility have led to its misuse for self-harm, especially in developing countries. This case series presents a comprehensive overview of three autopsies conducted on individuals with a history of paraquat ingestion. Clinically, paraquat intoxication is often challenging when history is not available. Autopsy findings across the cases showed congestion in major organs, with histopathological examinations revealing extensive damage, particularly in the lungs, liver, and kidneys, and unexpected cerebral effects. The discussion emphasizes the need for heightened safety protocols, increased awareness, and rigorous regulation to mitigate paraquat’s risks. These cases highlight the significance of thorough post-mortem investigations in aiding medical professionals in the management of paraquat poisoning and adding to the worldwide discussion on the safety and regulation of the herbicide.
Keywords: weedicide; paraquat; poisoning; histopathology; Suicide